Optimization of scAAVIL-1ra In Vitro and In Vivo to Deliver High Levels of Therapeutic Protein for Treatment of Osteoarthritis - Laurie R Goodrich; Jennifer N Phillips; C Wayne McIlwraith; Stacey B Foti; Joshua C Grieger; Steven J Gray; R Jude Samulski (Elsevier, 2013)
Osteoarthritis (OA) affects over 40 million people annually. We evaluated interleukin-1 receptor antagonist (IL-1ra) gene transfer in an equine model based on IL-1ra protein therapy which inhibits inflammation through blocking IL-1. Using the self-complementary adeno-associated virus (scAAV)IL-1ra equine gene as a starting construct, we optimized the transgene cassette by analyzing promoters (cytomegalovirus (CMV) versus chicken β-actin hybrid (CBh)), coding sequences (optimized versus unoptimized), vector capsid (serotype 2 versus chimeric capsid), and biological activity in vitro. AAV serotypes 2 and 2.5 CMV scAAVoptIL-1ra were tested in equine joints. We evaluated two doses of scAAVIL-1ra, scAAVGFP, and saline. We developed a novel endoscopy procedure and confirmed vector-derived transgene expression (GFP) in chondrocytes 6 months post-injection. AAVIL-1ra therapeutic protein levels were 200-800 ng/ml of synovial fluid over 23 and 186 days, respectively. No evidence of intra-articular toxicity was detected and no vector genomes were found in contralateral joints based on GFP fluorescence microscopy and quantitative PCR. Finally, we assayed vector-derived IL-1ra activity based on functional assays which supported anti-inflammatory activity of our protein. These studies represent the first large animal intra-articular gene transfer approach with a therapeutic gene using scAAV and demonstrate high levels of protein production over extended time supporting further clinical investigation using scAAV gene therapy for OA.